WhatsApp Group: Online Media for Early Childhood Learning during the Covid-19 Pandemic - Yusuf Hidayat; Taufik Hidayat; Arni Mariawati; Rosmiati Rosmiati; Vina Naba'ul Haq (CV. Tripe Konsultan, 2022)
During the Covid-19 Pandemic, learning is carried out from home through online system. This study aims to determine utilizing WhatsApp group as an alternative media of learning early childhood during the Covid-19 Pandemic. This research is carried out in an Islamic Kindergarten in Ciamis Regency. In this research, the writers then set forth two research questions: (1) How is the parents’ response in joining the online learning via WhatsApp group during the Covid-19 Pandemic? (2) What obstacles do the parents have in joining the online learning via WhatsApp group during the Covid-19 Pandemic? To answer the research questions, the researchers employ a qualitative descriptive study. The results of the present research show that utilizing WhatsApp group by the early childhood parents during the Covid-19 Pandemic is categorized good. It refers to the average percentage of 78%. It means that the early childhood parents accept in utilizing WhatsApp group as an alternative media of online learning during the Covid-19 Pandemic. In addition, the parents’ obstacles in joining the online learning via WhatsApp group during the Covid-19 Pandemic covers 3 points. Those are: 8% of the parents have obstacle in the internet access, 7% of parents have obstacle in the internet data, and 7% of parents have obstacle in the cell phone facility.